Characterisation of the vaginal microbiome in cervical intraepithelial neoplasia. (25th February 2016) - Mitra, Anita; MacIntyre, David; Lee, Yun; Smith, Ann; Marchesi, Julian; Lehne, Benjamin; Bhatia, Ramya; Lyons, Deirdre; Paraskevaidis, Evangelos; Li, Jia; Holmes, Elaine; Nicholson, Jeremy; et al.
Abstract: Background: Persistent infection with oncogenic human papillomavirus (HPV) is necessary for the development of cervical cancer. Although evidence indicates that the vaginal microbiome can have a functional role in the persistence or regression of HPV infections, this possibility has yet to be described in women with cervical intraepithelial neoplasia (CIN). We aimed to test the hypothesis that increasing microbiome diversity is associated with increasing CIN severity. Methods: Vaginal swabs were collected, and vaginal microbiome characterised by 16S rRNA gene sequencing (MiSeq, Illumina, San Diego, CA, USA). Women were categorised according to disease severity (invasive cervical cancer [ICC], high-grade squamous intraepithelial lesions [HSIL], low-grade squamous intraepithelial lesions [LSIL], and healthy controls) and HPV status and genotype. Multivariate modelling of sequence data was used to examine bacterial species classification data, and correlated to disease severity and HPV status and genotype. Findings: Hierarchical clustering analysis of bacterial species data revealed an association between increased disease severity and increased prevalence of microbiomes characterised by high-diversity and low levels of Lactobacillus spp (community state type CST IV), irrespective of HPV status (2 [10%] of 20 controls, 11 [21%] of 52 LSIL, 25 [27%]of 92 HSIL, ICC 2 [40%] of 5 ICC). Increasing disease severity was associated with decreasing relative abundance of Lactobacillus spp. The vaginal microbiome in women with HSIL was characterised by higher relative abundance of Sneathia sanguinegens (p<0·01), Anaerococcus tetradius (p<0·05), and Peptostreptococcus anaerobius (p<0·05), and lower levels of L jensenii (p<0·01) compared with women with LSIL. Interpretation: We show that women with CIN have a more diverse Lactobacillus -depleted vaginal microbiome, compared with healthy women. This finding supports previous reports indicating that a dysbiotic microbiome could be involved in HPV persistence. The vaginal microbiome can have a role in carcinogenesis and warrants further investigation. Future therapeutic strategies might allow modulation of the vaginal microbiome towards a vaginal community structure that promotes HPV clearance. Funding: Imperial College Healthcare Charity, British Society for Colposcopy and Cervical Pathology.